2019
DOI: 10.1016/j.surfcoat.2019.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal cycling frequency on the durability of Yb-Gd-Y-based thermal barrier coatings

Abstract: 2019). Effect of thermal cycling frequency on the durability of Yb-Gd-Y-based thermal barrier coatings. Surface and Coatings Technology. AbstractThe effects of thermal cycling frequency and buffer layer on the crack generation and thermal fatigue behaviors of Yb-Gd-Y-stabilized zirconia (YGYZ)-based thermal barrier coatings (TBCs) were investigated through thermally graded mechanical fatigue (TGMF) test. TGMF tests with low-(period of 10 min) and high-frequency (period of 2 min) cycling were performed at 1100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…Park et al suggested that plasma-sprayed YSZ coating using high purity feedstock exhibited greater phase stability and sintering resistance than the one using feedstock of regular purity [40]. Similarly, Lyu et al reported that double-layered TBC consisting of YGYZ top layer and high-purity YSZ buffer layer has better thermal and mechanical durability than its counterpart with regular-purity YSZ buffer layer in thermally graded mechanical fatigue test [30]. It can be seen from Table 4 that the impurity level of the 1400 • C calcined powder is very low, with the contents of most impurities not higher than 0.01%.…”
Section: Determination Of the Optimized Ygyz Calcined Powders For Pla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al suggested that plasma-sprayed YSZ coating using high purity feedstock exhibited greater phase stability and sintering resistance than the one using feedstock of regular purity [40]. Similarly, Lyu et al reported that double-layered TBC consisting of YGYZ top layer and high-purity YSZ buffer layer has better thermal and mechanical durability than its counterpart with regular-purity YSZ buffer layer in thermally graded mechanical fatigue test [30]. It can be seen from Table 4 that the impurity level of the 1400 • C calcined powder is very low, with the contents of most impurities not higher than 0.01%.…”
Section: Determination Of the Optimized Ygyz Calcined Powders For Pla...mentioning
confidence: 99%
“…Much work has been conducted on YGYZ; however, limited attention has been paid to its spray powder preparation, especially the novel and effective feedstock preparation method for air plasma spraying (APS), which is the most widely used technique for coating deposition. [24,27], Zhao et al used a conventional fusion and crushing method [28,29], while Jung et al directly purchased commercial powder [25,30]. A relatively long processing chain is inherent to the chemical coprecipitation method, while for fusion and crushing method, it is strenuous to crush the sintered bulk material with high hardness.…”
Section: Introductionmentioning
confidence: 99%
“…通过改进热障涂层材料体系 [1,[3][4][5][6] 、优化涂层结 构 [1,3,7] 、采用新型喷涂技术 [7][8] 可有效提升热障涂层 的性能。 其中, 低杂质含量的高纯度热障涂层 [2,5,[9][10] 因具有更好的抗烧结性、更长的耐热冲击寿命而被 广泛关注。 热障涂层的失效模式研究表明 [11][12] , TBCs 在服役过程中发生烧结, 将显著降低涂层的隔热效 果、应变容限及服役寿命 [13][14][15] 。Vaβen 等 [16] [17] 研究表明, 将高纯度 YSZ 和含有 Al 2 O 3 、SiO 2 杂质的 YSZ 涂层在 1400 ℃下进行热处理, 当杂 质含量从 0.1wt%~0.2wt%下降到 0.01wt%~0.05wt% 时, 涂层的烧结速率显著降低。Xie 等 [18] 提出杂质 含量的增加会加速相的分解。Helminiak 等 [19] [20][21] 。根据 Wang 等 [22] 的研究结果, 涂层中孔隙率对传热的影响最 大。涂层中存在的微裂纹和微气孔会大大降低涂层 的热扩散系数, 提高涂层隔热性能 [21] 。而涂层热扩 散系数的增大主要是由于 1400 ℃下 SiO 2 、Fe 2 O 3 促进了涂层的烧结和致密化 [23][24] [24] 。当 Al 2 O 3 含量增加到一定程度 时, 由于加入到涂层中的杂质促进了烧结, 提高了 涂层的致密度 [18] , 而这种效应对高温下涂层的热性 能起着更重要的作用 [20] , 进而引起涂层热扩散系数 的升高。 [28][29] , YSZ 体系中晶粒长大过程受阳离子扩散过程的影响, 部 分 Al 3+ 离子替代 Zr 4+ 离子, 为了维持电荷平衡, 阳 离子空位浓度及间隙浓度增加, 而间隙浓度为氧化 锆中扩散速率的控制环节, 进而促进晶粒长大, 并 改善了固相烧结 [30]…”
unclassified